2012
DOI: 10.1007/s00404-012-2383-6
|View full text |Cite
|
Sign up to set email alerts
|

Anterior colporrhaphy versus repair with mesh for anterior vaginal wall prolapse: a comparative clinical study

Abstract: Our data shows that repair with mesh is superior to anterior colporrhaphy with more satisfactory outcome to the patients. Due to the small size of our study and uncertainty of the long-term safety and resilience of the mesh, we recommend larger studies to confirm our preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
3
17
1
Order By: Relevance
“…Forty RCTs remained after removal of duplicates and studies not matching the eligibility criteria (Table 1 ). The indications for AC were urinary incontinence [ 10 12 ], pelvic organ prolapse [ 13 , 15 , 16 , 19 23 , 25 27 , 29 – 38 , 40 , 41 , 43 49 ] or both [ 14 , 17 , 18 , 24 , 28 , 39 , 42 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty RCTs remained after removal of duplicates and studies not matching the eligibility criteria (Table 1 ). The indications for AC were urinary incontinence [ 10 12 ], pelvic organ prolapse [ 13 , 15 , 16 , 19 23 , 25 27 , 29 – 38 , 40 , 41 , 43 49 ] or both [ 14 , 17 , 18 , 24 , 28 , 39 , 42 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In 12 studies (30.0%) fluid infiltration of the operating field was performed before the incision. A vasoconstricting solution was used in two studies (vasopressin in two [ 19 , 47 ], adrenaline in two [ 16 , 38 ]), and the type of agent used was not given in two studies [ 36 , 41 ]. A mixture of anesthetics and vasoconstricting solution was used in six studies (lidocaine and adrenaline in four [ 21 , 26 , 33 , 40 ], adrenalin and bupivacaine in two [ 22 , 31 ]).…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis showed that the use of meshes for the treatment of anterior vaginal wall prolapse is superior to native tissue surgical repair, when objective cure through POP-Q assessment is considered. [14][15][16][17][18][19][20][21][22][23][24][25] All of the articles included in this meta-analysis considered as an objective cure criterion a post-surgical POP-Q stage inferior to 2 in the pelvic examination. This definition of cure, that is, when the prolapse's maximum extent stays at least 1 cm above the hymenal ring, is based on the recommendations of the US National Institute of Health (NIH) workshop.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with apical fixation or concomitant apical surgery [71][72][73][74][75][76][77][78][79], anterior repair using a synthetic mesh (excluding Prolift ® and Perigee ® ) had a cumulative success rate of 93 %; the cumulative success rate of studies without apical fixation or without standard apical surgery [80][81][82][83][84][85][86][87][88][89] was 83 %. The cumulative rate of mesh erosion was 8 % (137/1740); the cumulative rate for chronic pain and de novo dyspareunia was 7% (59/846).…”
Section: Level Of Evidence 3 Grade Of Recommendation Bmentioning
confidence: 99%